1999
DOI: 10.3171/jns.1999.91.1.0059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of amygdala sclerosis in temporal lobe epilepsy

Abstract: Except for the relatively long history of epilepsy, the presence of AS is not associated with specific clinical or electrocorticographic features of mesial TLE. However, patients without AS are particularly at risk for deterioration of short-term verbal memory following amygdalohippocampectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 47 publications
1
26
0
1
Order By: Relevance
“…However, the epileptic foci in the participants in the current study were not located in the amygdala, which was confirmed by electrophysiological and surgical evaluations. Interestingly, a previous study was unable to find neuronal loss or the presence of gliosis in the amygdalae of patients with epilepsy whose epileptic foci were located outside the amygdala (Zentner et al, 1999). The influence of possible microscopic abnormalities in the amygdala on the participants in this study is, thus, considered to be minimal.…”
Section: Discussionmentioning
confidence: 88%
“…However, the epileptic foci in the participants in the current study were not located in the amygdala, which was confirmed by electrophysiological and surgical evaluations. Interestingly, a previous study was unable to find neuronal loss or the presence of gliosis in the amygdalae of patients with epilepsy whose epileptic foci were located outside the amygdala (Zentner et al, 1999). The influence of possible microscopic abnormalities in the amygdala on the participants in this study is, thus, considered to be minimal.…”
Section: Discussionmentioning
confidence: 88%
“…Future research will be required to disentangle the histopathological abnormalities in these amygdala lesions. It may be speculated that the progressively atrophic encephalitic amygdala lesions may end up as amygdala sclerosis 34 35. In line with this hypothesis is the observation that MTLE patients with amygdala atrophy on MRI had a history of encephalitis more frequently than MTLE patients with normal amygdala volumes 36…”
Section: Discussionmentioning
confidence: 93%
“…The considered measures were the number of correctly learned designs over 5 learning trials and recognition performance (corrected for false-positive answers). The test has been shown to be sensitive to right temporal lobe dysfunction, right mesiotemporal pathology, and also to right-sided temporal lobe surgery [36][37][38][39].…”
Section: Pre-and Postoperative Memory Assessmentmentioning
confidence: 99%
“…Analyses were based on learning performance (total number of words learned in five trials), delayed free recall, and recognition performance (corrected for false-positive answers). The test has been shown to be sensitive to left temporal lobe dysfunction, left mesiotemporal pathology and left-sided temporal lobe surgery [33][34][35][36].…”
Section: Pre-and Postoperative Memory Assessmentmentioning
confidence: 99%